Curcumin as Efflux Pump Inhibitor in Regulation of mexZ Expression and Enhancing Tobramycin Susceptibility in Resistant Pseudomonas aeruginosa Isolates - Kafi, Iftekhar Matloob; Abdulhasan, Ghusoon Ali (Iraqi Journal of Science, 2025)
This research aims to explore the potential of curcumin as an efflux pump inhibitor to potentiate the antibacterial activity of tobramycin against Pseudomonas aeruginosa. From a total of 175 samples, 93 isolates of P. aeruginosa were successfully isolated and identified through 16S rRNA confirmation. Disc-diffusion method was used to choose the most-resisted antibiotic. The minimum inhibitory concentration of antibiotic tobramycin alone and in combination with curcumin were evaluated by agar dilution method. The expression of mexZ was also analyzed using quantitative real time polymerase chain reaction in the presence of antibiotic and antibiotic with curcumin. The minimum inhibitory concentration of tobramycin alone ranged from 2048 to 1024 µg/ml, with the highest percentage (55%). However, when curcumin was added at 70μg/ml, there was a significant enhancement in the sensitivity (p≤ 0.05) of P. aeruginosa isolates to tobramycin. The highest percentage of isolates (22.5%) showed two-fold change in MIC followed by four-fold (12.5%), seven-fold (10%), three-fold (7.5%). Smaller changes ranging from 2.5-5% were also observed. when treated isolates with 1/2 MIC of tobramycin, resulting in downregulation in mexZ in all isolates as well as a clear significant increase (p≤ 0.001) in the expression of the mexZ in most isolates after using of curcumin with tobramycin. In conclusion, curcumin can decrease the minimum inhibitory concentration value of tobramycin in P. aeruginosa and can be used as a native compound to enhance the treatment of resistant isolates to tobramycin.